Analysis of the Geometrical Parameters and Factors which Define the Complexity and the Form of the Mold - Kochov, Atanas; Tuteski, Ognen; Spiroski, Zoran (Department for Production Engineering, Faculty of Technical Sciences, Novi Sad, Serbia, 2014)
Injection molding is a technology in which the tool costs present a significant factor of the total production costs. Therefore, research and development in the field of advanced design and production of molding has a decisive influence on the final product quality but also on the economy of the process. Current paper describes an iterative analysis which has been employed in order to perform an advanced mold design and construction. This analysis is based upon experimental results which take into account the complexity of the mold’s core and cavity as well as the geometry of the final product. A mathematical function has been developed in order to estimate the total costs of the mold.
Keywords: injection molding, total costs, mold geometry, mold complexity